desarrollo de un instrumento de telemedida para medición de potencia en módulo fotovoltaico de la UAN sede Manizales (2022)
In this project we designed a device known as telemetry which fulfills the function of measuring the energy generated by the loads in the photovoltaic installation of the UAN headquarters Manizales.the prototype was designed based on certain components known as current sensor, voltage regulator, protoboard among others. The prototype was designed based on certain components known as current sensor, voltage regulator, protoboard among others, which are connected directly to the panel and this sends a signal to a server in the cloud known as Node-Network to know the power consumed by the loads, with this project also seeks to cover a new type of technology that facilitates data collection in a new digital era and is environmentally friendly by not needing paper to know the power generated by the loads can send electronically the data collected.